STRENGTHENING RELATIONS AMONG IDEOLOGIES IN THE MIDST OF RELIGIOUS MOVEMENT CONFLICT IN GLADAK PAKEM JEMBER - Mahillah; Muhammad Faiz (Rausyan Fikr: Jurnal Ilmu Studi Ushuluddin dan Filsafat, 2023)
In a multicultural and diverse country like Indonesia, relations between religious movements sometimes encounter friction and conflict. This study will highlight the Imam Syafi'i Dirosat Islamiyah High School movement (STDI Imam Syafi'i) which has been established since 2007 with the initial name Ma'had Aly Imam Syafi'i. This Islamic educational institution is one of the Wahhabi ideology institutions in Jember Regency. According to the Wahhabis, Muslims are obliged to return to Islam, which is seen as pure, simple, and righteous, which is believed to be fully reclaimed by strictly carrying out the commands and example of the Prophet and strictly following correct ritual practices. These groups made the majority of the Jember community such as Nahdlatul Ulama (NU) followers feel uneasy about the existence of the STDI Imam Syafi'i campus with Wahhabi ideology. NU community feels that their existence is threatened as the majority group in Jember. Ideologically and religiously, Wahhabis and NU are very different. Many Nahdliyyin practices are considered heretical (bid'ah) by the Wahhabi group. Meanwhile, according to the community around the Imam Syafi'i STDI campus, it is different. The existence of the STDI campus provides a better economic impact for members around the campus. Since the campus has been operating, members' income has increased by opening food stalls, rented houses, and student boarding houses. The conflict started from differences in understanding in capturing religious arguments sourced from the Quran and Sunnah. The existence of interpretations, thoughts, and opinions of scholars (ijtihad) has triggered the understanding of Muslims. The attitude of NU members who are members of the TOPI Bangsa action in Jember shows the potential for conflict that can happen at any time. Considering that neither the security forces nor the local government have proven strong enough to anticipate open conflicts behind conflicting beliefs.